Kajian Dogmatis Tentang Tata Gereja Calvinis dan Implikasinya Bagi Jemaat GMIM Efrata Kanonang - Kimbal, Shania Britney; Sumakul, Henny W. B. (Educatio Christi, 2021)
This thesis discusses the Calvinist church order and its implications for the congregation of GMIM Efrata Kanonang. The Calvinist church order is a system that regulates the life and ministry of the church based on the teachings of John Calvin, and GMIM Efrata Kanonang is one of the churches that adopted the Calvinist church order. This thesis aims to find out the congregation's understanding of the meaning of the Calvinist church order and how it implies for the congregation of GMIM Efrata Kanonang. The implications for the congregation of GMIM Efrata Kanonang are analyzed through interviews, observations, and literature studies. It can be said that an understanding of the Calvinist church order can strengthen the congregation's faith foundation, increase awareness of God's sovereignty, and strengthen commitment to church discipline and biblical authority. In conclusion, this research presents the Calvinist church order and its implications for the congregation of GMIM Efrata Kanonang. It is hoped that the results of this study can provide valuable insights for the church in strengthening church practices and the spiritual growth of the congregation.